Keep IT simple – the challenge of interlaced IT architecture at Gothaer Systems. Issue 1 (May 2014) - Basten, Dirk; Joosten, Dominik; Mellis, Werner; Wallmueller, Cornelia
The German direct insurer Gothaer Insurance Group is among the largest insurance companies in Germany. In recent years, Gothaer was facing the challenge of replacing its existing collection systems. The replacement system was one of SAP's key modules for Insurance Solution, a standard software product called FS-CD (Financial Services-Collections and Disbursements). The first stage of the project significantly exceeded time and budget objectives. The second stage was expected to encounter serious technical problems. Consequently, the entire project was called into question. A meeting of the IT steering committee was scheduled at short notice to decide upon the project's continuance. This case chronicles the series of events leading to that upcoming steering committee meeting.